EVALUATION OF CHEMICAL COMPOSITION AND FEEDING VALUE OF FERMENTED JACKFRUIT (Artocapus heterophyllous) SEED MEAL USING RABBITS - O. O. Effiong; N. J. Paul; M. D. Udayi; A. F. Utin (Journal of Animal and Plant Sciences, 2024)
The majority of Nigerian population, particularly those living in rural communities can no longer afford animal protein in their daily meals due to the high cost of these products especially from conventional sources (cattle, sheep, and poultry) caused by high cost of feeds and feedingstuffs. This calls for dependence on alternative meat sources like rabbits which can survive mainly on forages with concentrates supplementation. Because of the high cost of maize, which is a source of energy in diets of rabbits, this study was therefore designed to evaluate the chemical composition of processed jackfruit seed meal and its feeding value as an alternative energy source. Bunches of jackfruits were harvested, the seed separated from the pulp and divided into four groups of 10kg each for fermentation. The maize cob solution prepared by mixing 100 gm of ash obtained after burning maize cob into 1 litre of distilled water in a plastic bowl was added to the first capped plastic bowl containing 10kg of cracked jackfruit seeds. The rumen digesta filtrate was poured into the second capped plastic bowl containing 10kg of jackfruit seed, and plain water was added to the jackfruit seed in the third bowl. Each sample was fermented at room temperature for 48 hours and thereafter rinsed, sun-dried, and milled using a 2 mm mesh hammer mill. Five diets were formulated with fermented jackfruit seed meals replacing maize in the control diet. Thirty-five weaned (ages between 4-5 weeks old), crossbred rabbits were used for the experiment. The experimental design employed was completely randomized. Data collected were subjected to analysis of variance using the General Linear Model (GLM) procedures of GenStat 14th edition. The results showed that rumen digesta filtrate fermentation media increased the crude protein from 5.34% in the raw jackfruit seed meal to 7.10%. The rumen digesta filtrate media reduced (P≤ 0.01) the concentration of phytates (3.17±0.56mg/100g), oxalates (34.10±0.58 mg/100g), tannins (1.64 mg/100g), relative to other media. Rabbits fed control diet recorded a significant (P≤0.01) higher average daily weight gain (11.36g), which was similar to 10.75g for rabbits on rumen digesta filtrate fermented jackfruit seed meal (RDFFJM) diet. The feed conversion ratio of 3.80 recorded for rabbits on (RDFFJM) diet was superior (P=0.001) compared to those recorded for other treatment diets. Rabbits fed plain water fermented jackfruit seed meal recorded the highest percentage of protein (34.4+2.08), ash (32.0+1.15), and fibre (56.3+1.15) digestibility. Most of the haematological and serum biochemical parameters were within the normal ranges. It was concluded that the rumen digesta filtrate fermented jackfruit seed meal diet enhanced the performance of the growing rabbits relative to the maize-based diet and other treatment diets.
Keywords: Rumen digesta filtrate; maize cob; fermentation; jackfruit; growing rabbits; anti-nutrients